Stimulation of Lung Innate Immunity Protects against Lethal Pneumococcal Pneumonia in Mice - Clement, Cecilia G; Evans, Scott E; Evans, Christopher M; Hawke, David; Kobayashi, Ryuji; Reynolds, Paul R; Moghaddam, Seyed J; Scott, Brenton L; Melicoff, Ernestina; Adachi, Roberto; Dickey, Burton F; Tuvim, Michael J (American journal of respiratory and critical care medicine, 2008)
The lungs are a common site of serious infection in both healthy and immunocompromised subjects, and the most likely route of delivery of a bioterror agent. Since the airway epithelium shows great structural plasticity in response to inflammatory stimuli, we hypothesized it might also show functional plasticity. To test the inducibility of lung defenses against bacterial challenge. Mice were treated with an aerosolized lysate of ultraviolet-killed nontypeable (unencapsulated) Haemophilus influenzae (NTHi), then challenged with a lethal dose of live Streptococcus pneumoniae (Spn) delivered by aerosol. Treatment with the NTHi lysate induced complete protection against challenge with a lethal dose of Spn if treatment preceded challenge by 4 to 24 hours. Lesser levels of protection occurred at shorter (83% at 2 h) and longer (83% at 48-72 h) intervals between treatment and challenge. There was also some protection when treatment was given 2 hours after challenge (survival increased from 14 to 57%), but not 24 hours after challenge. Protection did not depend on recruited neutrophils or resident mast cells and alveolar macrophages. Protection was specific to the airway route of infection, correlated in magnitude and time with rapid bacterial killing within the lungs, and was associated with increases of multiple antimicrobial polypeptides in lung lining fluid. We infer that protection derives from stimulation of local innate immune mechanisms, and that activated lung epithelium is the most likely cellular effector of this response. Augmentation of innate antimicrobial defenses of the lungs might have therapeutic value.